1999
DOI: 10.1142/s0218625x99000263
|View full text |Cite
|
Sign up to set email alerts
|

Molecules at Surfaces and Interfaces Studied Using Vibrational Spectroscopies and Related Techniques

Abstract: Recent developments in the major experimental vibrational-spectroscopic techniques (i.e. infrared absorption, Raman scattering, high resolution electron loss, helium atom scattering and sum frequency generation) are reviewed and illustrated with selected results. Particular emphasis is given to two important topics which have attracted much attention in recent years: (i) the complex surface reactions taking place on technologically relevant surfaces and interfaces, and (ii) vibrational dynamics with emphasis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 139 publications
(148 reference statements)
0
21
0
Order By: Relevance
“…Direct experimental measurement using ultrafast 2D vibrational echoes also showed that the spectral diffusion is indeed much slower and much more insignificant in the molecular monolayer in comparison to that in the bulk liquid [133,134]. Therefore, in the treatment of the surface vibrational spectral lineshape, the Bloch dynamics is usually a reasonable approximation of the surface vibrational dynamics, particularly for well packed molecular monolayers [61,100,101,139]. Thus, the vibrational spectral lineshape based on Bloch dynamics model will be explicitly discussed along with the development of the HR-BB-SFG-VS in this review.…”
Section: Sfg-vs As a Two-dimensional Nonlinear Spectroscopymentioning
confidence: 99%
“…Direct experimental measurement using ultrafast 2D vibrational echoes also showed that the spectral diffusion is indeed much slower and much more insignificant in the molecular monolayer in comparison to that in the bulk liquid [133,134]. Therefore, in the treatment of the surface vibrational spectral lineshape, the Bloch dynamics is usually a reasonable approximation of the surface vibrational dynamics, particularly for well packed molecular monolayers [61,100,101,139]. Thus, the vibrational spectral lineshape based on Bloch dynamics model will be explicitly discussed along with the development of the HR-BB-SFG-VS in this review.…”
Section: Sfg-vs As a Two-dimensional Nonlinear Spectroscopymentioning
confidence: 99%
“…Despite this importance, quantitative, direct measurements of the two coupled components, the adsorbate vibrational mode and the underlying electronic continuum, with adequate resolution and sensitivity are rare [1,2]. While the phonon side of the problem is now well studied [3], there has been to date little or no work to directly see the effect of adsorbate phonons on electronic states.…”
mentioning
confidence: 99%
“…It indicates that OH Ϫ ions in the solution can remove the defects of the rough surface 19 and some ͑111͒ facets might be developed on it. 17,18 This assumption can be supported by the previous IR results 10,17,18 that a strong band ͑even stronger͒ 18 in the region of 2000-2200 cm Ϫ1 can still be found by using IR on the Si͑100͒ surface after the treatment by a pH-elevated solution. The changing trend in band intensity is different due to the roughened silicon surface in our case can become smoother, while an atomically rough surface can remain in IR investigation.…”
Section: Resultsmentioning
confidence: 58%